2017
DOI: 10.4274/tdd.3307
|View full text |Cite
|
Sign up to set email alerts
|

Evaluations of Audiovestibular Manifestations in Patients with Psoriasis

Abstract: ÖzAmaç: Sensorinöral işitme kaybı, otoimmün ve inflamatuvar hastalıkların bir komplikasyonu olarak ortaya çıkabilmektedir. Psoriasis toplumda yaygın olarak görülmesine rağmen, odyolojik bozukluklar ile ilişkisi hakkında literatürdeki bilgiler sınırlıdır ve vestibüler bozukluklarla ilişkisi daha önce araştırılmamıştır. Biz de bu çalışmamızda, psoriasis hastalarında odyovestibüler bozuklukların varlığını ve hastalık parametreleri ile ilişkisini araştırmayı amaçladık. Yöntemler: Altmış bir psoriasis hastası ile y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
40
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(44 citation statements)
references
References 8 publications
2
40
2
Order By: Relevance
“…Different results were obtained in studies evaluating hearing in psoriasis patients. Temel et al 13 found that SNHL at high frequencies was significantly higher in psoriasis patients than in the control group. Hapa et al 18 reported that hearing thresholds at all frequencies were significantly higher in psoriasis patients compared to the control group.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…Different results were obtained in studies evaluating hearing in psoriasis patients. Temel et al 13 found that SNHL at high frequencies was significantly higher in psoriasis patients than in the control group. Hapa et al 18 reported that hearing thresholds at all frequencies were significantly higher in psoriasis patients compared to the control group.…”
Section: Discussionmentioning
confidence: 97%
“…The presence of joint involvement in patients with psoriasis may cause a more chronic inflammatory process and may adversely affect hearing. While the studies 7,9,10,13,18‐20 evaluating the hearing of patients with psoriasis have different results, the hearing has been reported to be negatively affected in all of the studies 6,8,12 evaluating hearing in patients with psoriatic arthritis. These results support our theory.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations